Financial Analysis in the Assessment of the Financial Condition of Football Clubs on the Example of Selected Clubs of the Polish Premier League - Jonas, Krzysztof; Pilch, Bartłomiej (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: The purpose of this paper is to examine the possibility of assessing the financial condition of football clubs using financial analysis methods, including models providing for bankruptcy risk.Research Design & Methods: The following are used: three-step studies, preliminary analysis for the outline of a general picture, indicative analysis for deepening the assessment, and discriminatory analysis to verify the situation of clubs.Findings: The analysis determined that an assessment of the financial condition of the entities audited was possible, including an indication of the entities at risk of bankruptcy.Implications / Recommendations: The financial analysis describes the situation of Polish football clubs so that an assessment of their financial condition could be formulated.Contribution: The paper creates the inspiration for further developing the study of the financial situation of football clubs from the point of view of different audiences.